Robot‐assisted laparoscopic continent cutaneous urinary diversion in adults: A single‐centre study - Thomas Loubersac; Etienne Lavallée; Benédicte Reiss; Marc Lefort; Pierre Kieny; Marc‐David Leclair; Jérome Rigaud; Loic Le Normand; Brigitte Perrouin‐Verbe; Chloé Lefevre; Marie‐Aimée Perrouin‐Verbe (BJUI Compass)
Abstract Objectives To show that robot‐assisted laparoscopic cutaneous continent urinary diversion (RALCCUD) is feasible and safe; however, data on clinical outcomes in adults are lacking. Materials and methods We conducted a retrospective study of all adults who underwent RALCCUD between 2017 and 2022 at a single tertiary reference centre. Patient characteristics, clinical information and perioperative outcomes were recorded. All patients underwent pre‐ and postoperative urodynamic evaluations. Functional outcomes were evaluated at 3 months, then yearly. Continence was defined as no stomal or urethral leakage. Results Twelve patients, mostly women (n = 11), median (IQR) age 47.4 (19–57) years underwent RALCCUD (four Mitrofanoff, four Yang‐Monti and four Casale). The main indication for surgery was inability to perform intermittent self‐catheterization through the native urethra. Eleven patients (92%) had neurogenic lower urinary tract disease caused by spinal cord injury or spinal dysraphism. Median (IQR) operative time was 313 (285–367) min. Four patients (33%) underwent concomitant procedures: three supratrigonal cystectomy (SC) with augmentation cystoplasty (AC) and one artificial urinary sphincter (AUS). No conversions to an open approach were required. Median (IQR) follow‐up was 51 (40–61) months. One early postoperative complication occurred (Clavien grade III). The late postoperative complication rate was 17%, with three complications occurring in three patients. At the last follow‐up, all patients could self‐catheterize through the tube, and the stomal and urethral continence rate was 100%. Conclusion RALCCUD is feasible and safe in adults, with a high rate of stomal and urethral continence and a low complication rate.